A3 Adenosine Receptor Allosteric Modulator Induces an Anti-Inflammatory Effect: In Vivo Studies and Molecular Mechanism of Action. (13th October 2014) - Cohen, Shira; Barer, Faina; Bar-Yehuda, Sara; IJzerman, Adriaan P.; Jacobson, Kenneth A.; Fishman, Pnina
Abstract : The A3 adenosine receptor (A3 AR) is overexpressed in inflammatory cells and in the peripheral blood mononuclear cells of individuals with inflammatory conditions. Agonists to the A3 AR are known to induce specific anti-inflammatory effects upon chronic treatment. LUF6000 is an allosteric compound known to modulate the A3 AR and render the endogenous ligand adenosine to bind to the receptor with higher affinity. The advantage of allosteric modulators is their capability to target specifically areas where adenosine levels are increased such as inflammatory and tumor sites, whereas normal body cells and tissues are refractory to the allosteric modulators due to low adenosine levels. LUF6000 administration induced anti-inflammatory effect in 3 experimental animal models of rat adjuvant induced arthritis, monoiodoacetate induced osteoarthritis, and concanavalin A induced liver inflammation in mice. The molecular mechanism of action points to deregulation of signaling proteins including PI3K, IKK, I κ B, Jak-2, and STAT-1, resulting in decreased levels of NF- κ B, known to mediate inflammatory effects. Moreover, LUF6000 induced a slight stimulatory effect on the number of normal white blood cells and neutrophils. The anti-inflammatory effect of LUF6000, mechanism of action, and the differential effects on inflammatory and normal cells position this allosteric modulator as an attractive and unique drug candidate.